The Contribution of Sir Maulana Abdur Rahim to Islamic Thought (On Women's and Workers Rights) - Akram Uddin; Rownok Jahan; Md Maruf Hasan (Journal of Comparative Study of Religions (JCSR), 2022)
Maulana Abdur Rahim was one of the leading Muslim scholars in the Indian subcontinent during mid-20th century. He is well known for his Intellectual thoughts through various writings, especially the Islamization of human knowledge. Most of his works are to refute Western ideologies on the basis of Islamic literature. This study aims to explore two significant ideas from his writings. Firstly, the article explores how Maulana Abdur Rahim compared and analyzed women's rights according to Islamic and secular worldviews. Especially, secular scholars often criticized by stating that Muslim women had no right to participate in social activities.  Abdur Rahim refuted this type of argument and wrote that Islam allows Muslim women to participate in social activities.  Women just need to follow some principles of Islam and Islam is comprehensive religion to protect the rights of women in the best manner. Secondly, this paper will examine how he portrayed the rights of workers in Islam in comparison with capitalist and Marxist ideologies. Especially he said that the rights of workers in socialist and capitalist societies had been violated. Moreover, the only owner of the whole world is Allah, and we are all his slaves (Bandha). That is why the prevailing social inequality between workers and employers has no place in Islam. The qualitative method is used to do content analysis from his writings to comprehend how he compared and came up with solutions for Muslim society which is affected by secular ideologies. This study has found that Maulana Abdur Rahim’s analysis in support of Islam can provide better and long-term effective solutions in comparison with the solutions that secular ideologies addressed for the rights for women and workers.